2021
DOI: 10.26434/chemrxiv.14245712.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Activation of PhICl2 with Pyridine

Abstract: <div>It has been previously proposed that pyridines can activate PhICl2 by displacing a chloride and forming the [PhI(Pyr)(Cl)]+ cation as a reactive intermediate. Here we show that pyridine does not displace chloride, but rather forms a weak complex with the iodine via halogen bonding along the C-I bond axis. This interaction is investigated by NMR, structural, charge density and theoretical investigations, which all indicate the pyridine does not activate PhICl2 as proposed.</div><div><b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In both cases methods to either thermodynamically or kinetically increase the activity of these reagents is desirable and successful reports include the utilization of Lewis acids and bases, silver salts and the generation of asymmetric intermediates in situ. [5][6][7][8][9][10][11][12] ArIX2 species where an X is OTf have been identified to have the highest oxidative potentials from a series of regular I(III) associated ligands making PhIX(OTf) species of particular interest. [13][14][15] Recently our group successfully isolated and structurally verified an ArI(OTf)2, NO2-PhI(OTf)2 (I1) by substituting the phenyl ring with a p-nitro substituent which successfully inhibited decomposition via electrophilic aromatic substitution (EAS) processes previously encountered on the phenyl moiety during attempts to access an ArI(OTf)2 species (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In both cases methods to either thermodynamically or kinetically increase the activity of these reagents is desirable and successful reports include the utilization of Lewis acids and bases, silver salts and the generation of asymmetric intermediates in situ. [5][6][7][8][9][10][11][12] ArIX2 species where an X is OTf have been identified to have the highest oxidative potentials from a series of regular I(III) associated ligands making PhIX(OTf) species of particular interest. [13][14][15] Recently our group successfully isolated and structurally verified an ArI(OTf)2, NO2-PhI(OTf)2 (I1) by substituting the phenyl ring with a p-nitro substituent which successfully inhibited decomposition via electrophilic aromatic substitution (EAS) processes previously encountered on the phenyl moiety during attempts to access an ArI(OTf)2 species (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…4-dimethylaminopyridine (4-DMAP) was also reported to catalytically activate PhICl 2 , but we have previously shown that 4-DMAP immediately reacts with PhICl 2 to give 3-chloro-4dimethylaminopyridine and protonated 4-DMAP as a chloride salt in an electrophilic aromatic substitution. 7,15 This means that in such a reaction all the 4-DMAP is consumed rather than acting as a catalyst. Investigating this aspect, addition of 20% 21 The additional chloride completes a square planar geometry about the iodine with a much longer I-Cl interaction than is found along the Cl-I-Cl bond axis in the parent compound.…”
mentioning
confidence: 99%